Dietary Flaxseed Oil Prevents Western-Type Diet-Induced Nonalcoholic Fatty Liver Disease in Apolipoprotein-E Knockout Mice. (7th September 2017) - Han, Hao; Qiu, Fubin; Zhao, Haifeng; Tang, Haiying; Li, Xiuhua; Shi, Dongxing
Abstract : The prevalence of nonalcoholic fatty liver disease (NAFLD) has dramatically increased globally during recent decades. Intake of n-3 polyunsaturated fatty acids (PUFAs), mainly eicosapentaenoic acid (EPA, C20:5n-3) and docosahexaenoic acid (DHA, C22:6n-3), is believed to be beneficial to the development of NAFLD. However, little information is available with regard to the effect of flaxseed oil rich in α -linolenic acid (ALA, C18:3n-3), a plant-derived n-3 PUFA, in improving NAFLD. This study was to gain the effect of flaxseed oil on NAFLD and further investigate the underlying mechanisms. Apolipoprotein-E knockout (apoE-KO) mice were given a normal chow diet, a western-type high-fat and high-cholesterol diet (WTD), or a WTD diet containing 10% flaxseed oil (WTD + FO) for 12 weeks. Our data showed that consumption of flaxseed oil significantly improved WTD-induced NAFLD, as well as ameliorated impaired lipid homeostasis, attenuated oxidative stress, and inhibited inflammation. These data were associated with the modification effects on expression levels of genes involved in de novo fat synthesis (SREBP-1c, ACC), triacylglycerol catabolism (PPAR α, CPT1A, and ACOX1), inflammation (NF- κ B, IL-6, TNF- α, and MCP-1), and oxidative stress (ROS, MDA, GSH, and SOD).